Long Term Results of Valve Operations in Patients with Diabetes - Huddleston, Stephen J.; Goheen, Erin; Opoku-Asare, Isaac; Kokkinos, Peter; Greenberg, Michael D.; Trachiotis, Gregory D. (Scientific Research, 2012)
Diabetes Mellitus (DM) adversely affects survival in patients with Coronary Artery Disease (CAD) undergoing Coronary Artery Bypass Grafting (CABG) surgery. The influence of diabetes on events after valve operations is less defined. We analyzed the effect of diabetes on short and long term outcomes in patients undergoing valvular operations. A total of 2200 patients had cardiac surgery at a single VA Medical Center between 1991 and 2008. 355 patients had undergone valve replacement or repair. Data documenting the presence of diabetes was collected prospectively and captured into the Veterans Affairs electronic medical record. Of the 355 patients who had a valvular operation, 259 (79%) had an Aortic Valve Replacement (AVR), 69 (20%) had a Mitral Valve Repair/Replacement (MVR), and 4 (1%) had a Tricsupid Valve Repair/Replacement (TVR), and 19% (n = 69) of all patients had diabetes. 44% of patients with DM and 38% of patients without DM had a combined valve and CABG procedure. During a total follow up of 18 yrs, 42 (60%) of patients with diabetes and 186 (65%) of patients without diabetes were alive (p = 0.118). At 1, 5, 10, 15 yrs survival in patients with versus without diabetes were 91% v 87%; 71% v 74%; 40% v 56%; 23% v 48% (p = NS). The presence of diabetes does not appear to adversely effect long-term survival in patients undergoing valve operations
Keywords: Cardiac; Heart Valve; Diabetes